The Challenges of Adapting a Questionnaire to a New Cultural Context: The Case of Studying Group-Based Guilt and Shame in Russia - Grigoryan, L.K.; Khaptsova, A.A.; Poluektova, O.V. (Kulʹturno-istoricheskai͡a︡ psikhologii͡a, 2018)
With the majority of social-psychological research still being conducted in Western countries, researchers from non-Western countries often adopt existing theories, constructs, and instruments that are not necessarily applicable to the contexts they are interested in. This paper discusses problems that might arise when transferring psychological constructs and instruments from one cultural setting to another. We use the case of a study of group-based guilt and shame in Russia that was carried out by the research team. First, we briefly discuss the original study and the problems we encountered while conducting it. We then analyze the results of eight in-depth semi-structured interviews that followed up the original study. Finally, we conduct a thematic analysis of Facebook commentaries (N=98) that participants left after filling out the original questionnaire. Based on these analyses, we suggest a checklist for researchers who plan to study a psychological construct that wasn’t studied in a given cultural context before. With this paper, we hope to highlight the importance of thorough and comprehensive adaptation of psychological constructs and instruments to new cultural settings. В статье представлены результаты качественного исследования, целью которого является анализ трудностей, с которыми могут столкнуться исследователи при переносе психологических конструктов и измерений из одного культурного контекста в другой. Анализ проведен на основе обратной связи, полученной в ходе исследования коллективных эмоций вины и стыда в России. Одной из задач статьи является привлечение внимания исследователей к важности тщательной и всесторонней адаптации конструктов и инструментов к новым культурным контекстам. В статье представлено краткое описание нашего исследования и проблем, возникших в ходе его проведения. Проанализированы результаты восьми глубинных интервью, проведенных по следам исследования, а также публичные комментарии пользователей сети Facebook (N = 98), оставленные респондентами после заполнения опросника. В качестве выводов мы предлагаем своеобразный «лист самоконтроля» для исследователей, которые проводят кросс-культурные исследования или впервые изучают какой-либо психологический конструкт в новой культурной среде.